1993
DOI: 10.1007/bf00005975
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and substrate preference of brown trout in a littoral zone

Abstract: SynopsisWe studied vertical distribution, substrate preference and food choice of brown trout, Salmo trutta, from benthic gillnet catches at four littoral sampling locations in a Norwegian hydroelectric reservoir. The sampling locations had different bottom substrates; at one location the bottom substrate consisted of sand, while at the other three, substrates consisted of stones ranging 2-5 cm, 10-30 cm and 30-150 cm in diameter, respectively. Small-sized (< 160cm) and intermediate-size (160-269mm) brown trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Sandy bottom without any shelter was avoided, due to low catch probability (Hegge, Hesthagen & Skurdal 1993). To enhance the possibilities of catching juvenile salmonids in the lakes, we concentrated the investigations to the shallow littoral zone (0-3 m depth).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandy bottom without any shelter was avoided, due to low catch probability (Hegge, Hesthagen & Skurdal 1993). To enhance the possibilities of catching juvenile salmonids in the lakes, we concentrated the investigations to the shallow littoral zone (0-3 m depth).…”
Section: Samplingmentioning
confidence: 99%
“…To enhance the possibilities of catching juvenile salmonids in the lakes, we concentrated the investigations to the shallow littoral zone (0-3 m depth). Sandy bottom without any shelter was avoided, due to low catch probability (Hegge, Hesthagen & Skurdal 1993). Fishing was carried out at night (20.0Cr08.00 hours).…”
Section: Samplingmentioning
confidence: 99%
“…Some studies have reported that small-sized brown trout mainly live in littoral habitats, while larger individuals occupy the pelagic zone (Hegge et al 1993;Hesthagen et al 1997), and larger individuals are more capable of migration across habitat boundaries for foraging (Grey 2001). Small anchovies occupy littoral habitats for more favorable feeding and to reduce the risk of being preyed upon (Bacha and Amara 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Brown trout in the study lake are spatially segregated according to size, as all individuals with body lengths of <20 cm are restricted to the epibenthic habitat, whereas larger specimens use the upper strata of pelagic waters to some extent (Hesthagen & Gran 1997). However, the spatial segregation of brown trout occurs gradually according to size (Hegge et al 1993b); smaller brown trout in the littoral zone took a position close to the bottom, whereas larger specimens were found at greater distances from the bottom, thus improving their access to valuable zooplankton and surface insects. The competition among smaller brown trout in the littoral zone of Lake Vinsteren seems to be relatively severe, as indicated by their condition factor of only 0.90, compared with 1.0-1.4 for larger fish (Hesthagen & Johnsen 2006).…”
Section: Discussionmentioning
confidence: 99%